SUBJECTIVE WELL-BEING AND FLOURISHING AT WORK: THE IMPACT OF PROFESSIONAL FULFILMENT - OLIVEIRA-SILVA,LIGIA C. (2021)
ABSTRACT Purpose: The main purpose of this study was to investigate the impact professional fulfilment has on aspects of positive psychology, such as subjective well-being and flourishing at work. Originality/value: We analyse whether professional fulfilment, as a career aspect, influences only work factors, such as flourishing, or if it also contributes to subjective well-being in life. Additionally, few studies have focused on professional fulfilment because of its novelty. Therefore, this study contributes to advancing a new concept, as well as to the development of new models and theories in positive psychology. Design/methodology/approach: This is a quantitative, survey-type research study involving 358 participants who have a wide variety of jobs and professions. The questionnaire presented subjective well-being, flourishing at work and professional fulfilment scales, as well as socio-demographic questions. Data were analysed using bivariate correlations and multiple regression analysis. Findings: Results indicated that professional fulfilment predicts higher subjective well-being and flourishing at work. Therefore, the more people perceive they have achieved what they value in their career and demonstrate positive goal progress, the more they experience well-being in life in general and the more they flourish at work. There are major positive relationships between career goals, well-being and flourishing at work, which is consistent with previous studies. Future studies could analyse under which specific contextual conditions the pursuit of career goals has a higher or lower impact on subjective well-being and flourishing.